Research on wave set-up during storms along the coast of Cua Dai, Hoi An - The, Nguyen Ngoc; Dien, Duong Cong; Tung, Tran Thanh (Vietnam Journal of Marine Science and Technology, 2019)
The central coast of Vietnam is frequently prone to storms and floods. Aside from wind damages during storms, the effect of storm surges, which includes wave set-up, on the coast and coastal infrastructures is very severe. Therefore calculation and prediction of wave set-up and storm surges are significant, both scientifically and practically, to serve as scientific bases for sustainable coastal planning, development and protection. This paper presents the study results on nearshore wave propagation and transformation, as well as the distribution of wave set-up during storms in the coastal area of Cua Dai, Hoi An, using SWAN and SWASH models. The models are thoroughly tested against wave and water level data series collected during a campaign in the project framework. The simulation results show the overall picture of the nearshore wave field and the surge height induced by waves during a storm event along Cua Dai, Hoi An coast. The research output also indicates that wave set-up contributes an important part to the extreme water level of the local nearshore area during storms.